Kontribusi Budaya Suku Yali bagi Pola Pengajaran Mahasiswa Asal Yalimu di STFT GKI I.S. Kijne Jayapura - Sientje Latuputty; Maria Niester Insoraki Komboy; Lisa Marpaung (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2026)
This study aims to examine and analyze the contribution of Yali culture to teaching patterns for Yalimu students at STFT GKI I.S. Kijne Jayapura. This study used a qualitative approach with ethnographic methods. The results showed that Yali cultural values, such as oral traditions, collectivity, practice-based learning, communal relations, and the use of nature as a learning space, have a significant influence on how students understand and construct academic knowledge. Teaching patterns that emphasize theory, written traditions, and a uniform approach tend to create learning barriers for Yalimu students. In contrast, the application of participatory, thematic, small-group-based, and contextual learning methods has been shown to improve student understanding of the material, self-confidence, and active involvement in the teaching and learning process. This study recommends the need to develop teaching patterns that are responsive to students' cultural backgrounds, as well as the development of patterns and theories that start from within, based on one's own experience and culture.